SIDBI Report on Small Scale Industries Sector 1999 - Planning Commission (Planning Commission, 1999)
The SIDBI Report (1999) on the Small Scale Industries (SSI) sector provides a comprehensive overview of the evolution, structure, performance, and policy framework governing this crucial segment of the Indian economy. Beginning with early industrial policies of 1948 and 1956, the report traces the development strategy that emphasized import substitution, public sector dominance, and extensive regulatory controls, which were later liberalized through the economic reforms of 1991 that reduced industrial licensing and encouraged private and foreign investment. Despite fluctuations in industrial growth, the SSI sector has remained a vital contributor, accounting for a significant share of industrial units, manufacturing output, exports, and employment, while also acting as a breeding ground for entrepreneurial talent. The sector encompasses a diverse range of enterprises from traditional handicrafts to modern industrial units, supported through priority sector lending, concessional finance, and various government initiatives. Over time, structural shifts such as the dominance of proprietorship firms and the emergence of both modern and traditional subsectors have been observed. The report highlights the role of institutional frameworks, including agencies like SIDBI, SIDO, RBI, and various state-level bodies, in promoting credit access, infrastructure development, and policy coordination. It also discusses the importance of reliable data, challenges in the unorganised sector, and the relative efficiency of SSIs compared to large industries, particularly in terms of capital productivity. Policy initiatives have focused on protection, modernization, technology upgradation, export promotion, and cluster development, while also encouraging rural industrialisation and women entrepreneurship. The multi-agency credit structure, including banks and financial institutions, has evolved to meet the financial needs of the sector, with special emphasis on micro credit as a tool for poverty alleviation and empowerment. Overall, the report underscores the SSI sector’s critical role in driving industrial and economic growth, generating employment, and fostering balanced regional development in India.
Small Industries Development Bank of India
Small Industries Development Bank of India
Keywords: Small Scale Industries, Industrial Policy, Economic Reforms, Industrial Growth, Entrepreneurship Development, Priority Sector Lending, Credit Dispensation, Institutional Support, Industrial Clusters, Rural Industrialisation, Technology Upgradation, Micro Credit